Integrating postpartum IUD counselling and insertion into routine maternity care in Nepal: Assessing trends over time - Mahesh Chandra Puri; Muqi Guo; Lucy Stone; Iqbal H. Shah (Public Library of Science (PLoS), 2023)
To meet the postpartum family planning (PPFP) needs of women in Nepal, an intervention was launched to integrate PPFP counselling and postpartum IUD (PPIUD) insertion into maternity care. Women delivering in study hospitals over a period of 18 months were interviewed at the time of delivery and at 15 months following the end of the study enrollment period to assess if the impact of the intervention observed at the end of the study was maintained. Data were collected prior to the intervention, at the middle month of the intervention roll out, at the end of the enrollment period and 15 months after the end of the enrollment period. We compared PPFP counselling and insertion rates before, during, at the end of and after the intervention study period, using cross-tabulation and chi-square tests. Overall, PPFP counselling rates increased from 11% at the baseline month to 45% at the end of the enrollment in February 2017 and remained the same 15 months later in July 2018. PPIUD uptake, however, rose from a negligible 0.1% at the baseline to 4.3% in February 2017, but declined to 3.4% in July 2018. PPIUD uptake among women who were counselled showed a similar trend, increasing from 1.9% at the baseline to 9.6% in February 2017 and declining to 6.0% in July 2018. The intervention had an appreciable continued impact on PPIUD counselling rates and although PPIUD uptake rose during the intervention, this trend was not observed in the 15 months post-study follow up. The impact of the intervention was greater and persistent in hospitals that had a longer period of exposure to intervention. The results suggest that counselling was well integrated with the maternity care, though uptake of PPIUD dropped after intervention activities such as active monitoring, technical supervision, provision of IUDs and training were withdrawn. Trial registration: This study has been registered with Clinical Trial.gov. The registration number is NCT 02718222. Details about the study design have been published by Canning et al, 2016.